AKTIVITAS ANTIOKSIDAN KOMBINASI EKSTRAK CAIR TEH HITAM (Camellia sinensis) DAN AIR LEMON (Citrus limon) - Yanuarti, Rini; Muziburohman, Dede; Fajar, In Rahmi Fatria (Pusat Unggulan Iptek Ketahanan Pangan Universitas Sultan Ageng Tirtayasa, 2024)
Tea (Camellia sinensis) is a drink that is one of the favorites of Indonesian people. Black tea contains polyphenol compounds which act as antioxidants. The compound components of lime fruit (Citrus limon) have antioxidant activity. The brewing process is very beneficial because antioxidant compounds are obtained optimally and can maintain the quality of chemical compounds. The aim of this research was to determine the interaction based on the results of antioxidant activity tests on a combination of black tea liquid extract and lemon juice. This research is included in the experimental design carried out at the Tarumanagara University Laboratory, Cilandak, South Jakarta. The research methods used included phytochemical screening, ash content test, total flavonoid test and antioxidant test using SNI 01-1902-1995 tea brewing standards. The research results showed that the phytochemical screening combination of black tea liquid extract and lime juice contained flavonoid, saponin, tannin and terpenoid compounds. The ash content in black tea liquid extract has a value of 0.34%. The presence of flavonoid compounds which have a value of 472.115 mgQE/g extract indicates antioxidant activity. The combination of black tea liquid extract and lemon water has antioxidant activity. The combination of black tea A: lemon water (1:1) is included in the moderate antioxidant category with an IC50 value of 135.103 ppm and an AAI value of 0.740. The combination of black tea C: lemon water (2:1) gets an IC50 value of 74,742 ppm and an AAI value of 1,337, which is included in the strong antioxidant category. The combination of sample B black tea: lemon water (1:2) got an IC50 value of 105,400 ppm and an AAI value of 0.948, including the moderate antioxidant category. Keywords: Antioxidants, Lime juice, Black tea